A influência do país de origem na escolha de marcas desconhecidas: uma investigação sobre os atributos de marca de materiais esportivos - Meirelles, Franklin de Souza (2015)
This study aims at the empirical verification of the possible influence of country of origin (COO) in consumer choice by a particular sporting goods brand, other attributes such forward which name brand elements / logo, response time to market and Brand disclosure. Through the understanding of the concept of brand attributes and a literature review on the influence of country of origin as attribute and variable choice, the importance of sponsorship in the development of brand equity, and less prominent attributes of interference, it was conducted a survey of foreign brands of sports equipment unknown to the Brazilian public to understand how the attributes presented influence the perception and consumer intentions. Using the experimental technique as a research tool, from three experiments that combined country of origin and other attributes in a 2x2 combination, we obtained 360 responses considered valid and the main findings refer to the partial effect of country of origin variable decision and the irrelevance of attributes such as longevity of the brand, the attractiveness of the name / logo and the fact the brand sponsor any sports organization, when in conjunction with the Country. Involvement presented important role as moderator of the decision variables, reducing the effect of the Country of Origin in the choices.